A fully automated microfluidic micellar electrokinetic chromatography analyzer for organic compound detection. Issue 18 (10th August 2016) - Jang, Lee-Woon; Razu, Md Enayet; Jensen, Erik C.; Jiao, Hong; Kim, Jungkyu
Abstract : A fully automated micellar electrokinetic chromatography analyzer is developed using Lifting-Gate microvalves, vacuum-driven washing system, and capillary zone electrophoresis chip. Abstract : An integrated microfluidic chemical analyzer utilizing micellar electrokinetic chromatography (MEKC) is developed using a pneumatically actuated Lifting-Gate microvalve array and a capillary zone electrophoresis (CZE) chip. Each of the necessary liquid handling processes such as metering, mixing, transferring, and washing steps are performed autonomously by the microvalve array. In addition, a method is presented for automated washing of the high resistance CZE channel for device reuse and periodic automated in situ analyses. To demonstrate the functionality of this MEKC platform, amino acids and thiols are labeled and efficiently separated via a fully automated program. Reproducibility of the automated programs for sample labeling and periodic in situ MEKC analysis was tested and found to be equivalent to conventional sample processing techniques for capillary electrophoresis analysis. This platform enables simple, portable, and automated chemical compound analysis which can be used in challenging environments.